(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the issues of air conditioning of indoor air in schools and preschool educational institutions not supplied with natural gas from the point of view of the engineering communications system. The main attention is paid to the use of solar energy, which is a renewable energy source. The possibilities of integrating solar panels and solar energy devices into heating, ventilation and cooling systems are considered, and aspects of their construction and installation are highlighted. The results of the study show that it is possible to increase the energy independence of educational institutions in areas where gas is not available and to ensure an environmentally safe indoor air environment.